2020
DOI: 10.1136/bcr-2019-232896
|View full text |Cite
|
Sign up to set email alerts
|

Ofatumumab for multirelapsing membranous nephropathy complicated by rituximab-induced serum-sickness

Abstract: Rituximab (375 mg/m2) achieved remission of the first episode and six relapses of nephrotic syndrome (NS) in a young male patient with podocyte phospholipase A2 receptor (PLA2R)-related membranous nephropathy (MN) refractory to steroids and cyclosporine. Between-treatments interval averaged 17.4±4.2 months. The seventh infusion was complicated by delayed serum-sickness, which resolved with steroids. On subsequent relapse, the fully human anti-CD20 monoclonal antibody ofatumumab (300 mg) achieved remission of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 36 publications
1
47
0
Order By: Relevance
“…New anti-CD20 humanized antibodies are now on the market. They have several advantages over rituximab such as low risk of immunization against the monoclonal antibody and prolonged B-cell depletion.Several case reports and case series have shown that these new antibodies (ofatumumab, obinutuzumab, ocrelizumab) could be effective in refractory or multi-relapsing MN as well as in the patients treated with rituximab that developed serum sickness [ 23 , 24 , 25 , 26 ]. Since in about 30% to 40% of patients, rituximab fails to induce remission of MN and relapses are frequent, these more potent biotherapies will most likely take a substantial part in severe forms of MN in a near future.…”
Section: Perspectivesmentioning
confidence: 99%
“…New anti-CD20 humanized antibodies are now on the market. They have several advantages over rituximab such as low risk of immunization against the monoclonal antibody and prolonged B-cell depletion.Several case reports and case series have shown that these new antibodies (ofatumumab, obinutuzumab, ocrelizumab) could be effective in refractory or multi-relapsing MN as well as in the patients treated with rituximab that developed serum sickness [ 23 , 24 , 25 , 26 ]. Since in about 30% to 40% of patients, rituximab fails to induce remission of MN and relapses are frequent, these more potent biotherapies will most likely take a substantial part in severe forms of MN in a near future.…”
Section: Perspectivesmentioning
confidence: 99%
“…On subsequent relapse, ofatumumab (300 mg) achieved remission of the NS, without significant side effects. Overall, this patient received 3 times ofatumumab in approximately four years interval, and one year after the second injection he experienced viral enteritis with high-grade fever and finally with the third infusion of ofatumumab, partial remission was achieved (13).…”
Section: Discussionmentioning
confidence: 92%
“…One patient had post-transplant recurrent FSGS (6,11). Gastrointestinal complications such as nausea, vomiting, and abdominal pain were reported in some studies (1,13,16).…”
Section: N 5 Study Selectionmentioning
confidence: 95%
See 1 more Smart Citation
“…Two patients had persistent nephrotic-range proteinuria while one had partial remission. In a more recent case report [21] on an 18-year-old boy with PLA2R-related MN refractory to steroids/CSA, remissions were achieved with RTX. The seventh dose of RTX was complicated by infusion-related reaction then delayed serum-sickness, which resolved with steroids.…”
Section: Membranous Nephropathymentioning
confidence: 99%